(untitled) (Heritage, 2020)
The author points out the Austro-Hungarian influence on the Catholic Arbanasi - fandas in Prizren and Peć Sanjak in the early 20th century. Austro-Hungarian activity in this field intensified after the Serbo-Turkish wars and the Congress of Berlin. Violence against the Serbian population had since become more frequent, aided by the fandas that have the support and protection of Roman Catholic priests and Austro-Hungarian diplomats.TheCatholicArbanasipeople commit various forms of zulum over Serbain people, who powerless before them abandoned their properties. A large number of Serbian properties were getting new owners – fandas, that were settled with the permission of the beys.The Austria-Hungary, wishing to cause as much disorder as possible, incited the fandas and MohammedanArbanasipeople against the Serbian people, in whom they saw the main obstacle to the achievement of their aims and the occupation of these regions.The situation demanded greater involvement of Serbian and Russian diplomacy in protecting the thinned-out Serbian population in Peć and Prizren sanjak.